2014
DOI: 10.7895/ijadr.v3i2.147
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and health care utilization in rural Liberia: Results of a community-based survey for basic public health indicators

Abstract: Aim: To measure the association between alcohol use and health-seeking behavior in post-conflict Liberia.Design: Cross-sectional survey.Setting: A community in rural southeast Liberia, from January 11 to January 16, 2010Participants: 600 heads-of-household. Measures:Logistic regression models for estimation of associations between alcohol use and indicators of healthcare utilization. Frequent alcohol use was defined as drinking more than seven days out of the last two weeks.Findings: Frequent alcohol use was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Second, the current study found that among Chinese adults, people who regularly drank alcohol were less likely to use outpatient and inpatient care than non-regular drinkers. The result is consistent with findings for American drinkers [19], rural Liberia drinkers [20], and German drinkers [37]. Three possible reasons may explain the inverse relationship between regular drinking and healthcare utilization: firstly, people who regularly drink alcohol may not care about their health status or maybe risk-tolerant individuals [22,38].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Second, the current study found that among Chinese adults, people who regularly drank alcohol were less likely to use outpatient and inpatient care than non-regular drinkers. The result is consistent with findings for American drinkers [19], rural Liberia drinkers [20], and German drinkers [37]. Three possible reasons may explain the inverse relationship between regular drinking and healthcare utilization: firstly, people who regularly drink alcohol may not care about their health status or maybe risk-tolerant individuals [22,38].…”
Section: Discussionsupporting
confidence: 86%
“…Some studies presented that problematic alcohol users are associated with higher healthcare utilization, including outpatient visits, emergency services, and hospitalization compared to abstainers [15,16]. In contrast, many studies found that alcohol users are associated with lower health care use than abstainers [14,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, although highly remote populations are rarely study populations, they are fairly common in many countries across the continent. Second, objectively measured distances are often dichotomized into closer and farther populations [ 16 , 35 ], which obscures the effect of farther distances. Finally, many studies use self–reported distance or travel time, which frequently suffer from imprecision 16 and would likely bias the measured association toward the null.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that problematic alcohol users are more likely to use health care, including outpatient visits, emergency services, and hospitalization, than abstainers [ 18 , 19 ]. In contrast, many studies have found that alcohol users are less likely to use health care than abstainers [ 17 , 20 23 ].…”
Section: Introductionmentioning
confidence: 99%